2017
DOI: 10.1556/030.64.2017.005
|View full text |Cite
|
Sign up to set email alerts
|

Biofilm formation of Achromobacter xylosoxidans on contact lens

Abstract: Achromobacter spp. may contaminate lenses, lens cases, and contact lens solutions and cause ocular infections. The aim of this study was to investigate the possibility of isolated strain of Achromobacter xylosoxidans to form biofilm on the surface of soft contact lenses (CL), to quantify the production of the formed biofilm, and compare it with the reference strains (Pseudomonas aeruginosa, Staphylococcus aureus, and Haemophilus influenzae). Bacterial strain isolated from one contact lens case was identified a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 22 publications
0
6
0
1
Order By: Relevance
“…Similarly to other non-fermenting Gram-negative bacteria, Achromobacter species have a plethora of intrinsic resistance mechanisms: penicillins, 1-2 nd generation cephalosporins, chloramphenicol, macrolides and aminoglycosides [4][5][6][7][8][9][10][11][12][13]17,31,32]. Fluoroquinolones are usually considered as the part of a combination regimen (not as monotherapy) with carbapenems, therefore IMP, MER, TZP and SXT are the drugs of choice in these infections, preferably in combination.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly to other non-fermenting Gram-negative bacteria, Achromobacter species have a plethora of intrinsic resistance mechanisms: penicillins, 1-2 nd generation cephalosporins, chloramphenicol, macrolides and aminoglycosides [4][5][6][7][8][9][10][11][12][13]17,31,32]. Fluoroquinolones are usually considered as the part of a combination regimen (not as monotherapy) with carbapenems, therefore IMP, MER, TZP and SXT are the drugs of choice in these infections, preferably in combination.…”
Section: Discussionmentioning
confidence: 99%
“…This lifestyle can protect bacteria against potential environmental stress, such as antibiotics and host defense components (Hall and Mah, 2017; Tseng et al, 2018). In the clinical situation, biofilm formed by pathogenic bacteria can establish themselves on human surfaces or medical devices, including implants, catheter, endotracheal tubes and others (Rieger et al, 2016; Konstantinović et al, 2017; Kenaley et al, 2018; Silva et al, 2018). Biofilm formation on these surfaces can serve as a source of infection.…”
Section: Preventing Biofilm Formation and Affecting The Biofilm Strucmentioning
confidence: 99%
“…Achromobacter xylosoxidans has been documented to form biofilms on plastics, including on contact lenses, urinary and intravenous catheters, and reusable tissue dispensers treated with disinfectant solution. [4][5][6] One study demonstrated that A xylosoxidans is even capable of biodegradation of plastic, using the plastic as its sole source of carbon. 7 Our case illustrates an indolent infection with A xylosoxidans forming a granulomatous abscess at the site of an insulin pump that was left in place for 7 days in an immunocompetent patient.…”
Section: Commentmentioning
confidence: 99%